Analisis Drug Related Problems Pada Pasien Benign Prostatic Hyperplasia (BPH) di RSUD Arifin Achmad Provinsi Riau - Nugraha, Dimas Pramita; Afdal, Afdal; Pratama, Anggit Armedo; Kemala, Sandrina (Buletin Farmatera, 2021)
The prevalence of Benign Prostatic Hyperplasia (BPH) is progressive and increases linearly with age. In addition to the high prevalence of comorbid diseases in the elderly population, patients with BPH are more likely to be prescribed a variety of drugs, which leads to an increased risk of drug interactions, BPH patients are at risk of developing drug-related problems (DRP). This study aimed to analyze DRP-related factors in BPH patients. This research is a retrospective study conducted at Arifin Achmad Hospital, Riau Province, with data taken from January 2017 to December 2019. DRP classification uses Pharmaceutical Care Network Europe Classification Version (PCNE) 5.01. The relationship between categorical variables was analyzed using Pearson's chi-square. In this study, most of the patients were old age (73.9%), ethnic Malay (31.9%). Clinical characteristics of BPH patients 84.5% had a period of suffering from BPH less than 1 year, the most common BPH complications were hematuria at 34.3% and the most comorbid disease was hypertension 26.6%. Most of the patients used alpha-blocker monotherapy (89.3%). There were a total of 40 DRPs, the most common DRP category was interaction problems in the form of potential drug interactions (97.5%) followed by drug selection problems in the form of incorrect duplication in the therapy group (2.5%). Factors that were significantly associated with the occurrence of DRP in BPH patients were complications of BPH (p = 0.007, RR = 2.77), hypertension (p = 0.011, RR = 2.04), and polypharmacy (p = 0.00, RR = 4, 79). This study indicates that there is still DRP in BPH patients, especially concerning potential drug interactions. Undetectable DRP can cause drug-related morbidity and if not attended to or treated, it can lead to a drug-related death.